La «Traduction» du Théâtre au Cinéma: Quelques Exemples du Répertoire Canadien - Loiselle, André (Theatre Research in Canada / Recherches théâtrales au Canada, 2003)
Generally, film adaptations of drama do not follow the principles of translation. There are too many differences between the original and the film version for the term “translation” to be applicable. However, there are a few cases where it can be said that a film actually translates a play. This article examines a number of adaptations of Canadian plays, in the light of various translation theories as well as narratological approaches, to draw a conceptual line between adaptation and translation. As is demonstrated, while Lilies, Les muses orphelines and Il était une fois dans l’Est cannot be read as translations of plays by Michel Marc Bouchard and Michel Tremblay, Tectonic Plates and Gapi can productively be studied as translations of original works by Théâtre Repère and Antonine Maillet. In the process, the author hopes to establish the basic charateristics of filmic translation.